2021
DOI: 10.1007/s11628-021-00459-4
|View full text |Cite
|
Sign up to set email alerts
|

Infusing tribal reciprocity into service research: towards an integrated and dynamic view of repayment, retaliation and restorative justice for regenerative service ecosystem wellbeing

Abstract: Service exchange among actors and the notion of reciprocity have gained momentum in service research. However, reciprocity's underlying facets and nature have been neglected. Drawing on a tribal notion of dynamic reciprocity facilitates the understanding of contemporary service interactions in service ecosystems. We explore reciprocity's tribal elements of repayment, retaliation and restorative justice. This tribal view of reciprocity is also linked to relational and regenerative wellbeing. We derive a concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…For example, Frow et al (2016) define service ecosystem well-being as the efficiency and effectiveness of the ecosystem. Empirically, the work in service ecosystems well-being focuses on how different factors affect the performance of the service ecosystem, specifically its ability to balance challenges and resources to maintain viability (Brodie et al , 2021; Finsterwalder and Tombs, 2021). An exception, Baccarani and Cassia (2017) show how resource integration affects service ecosystem well-being and the well-being of specific focal actors (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Frow et al (2016) define service ecosystem well-being as the efficiency and effectiveness of the ecosystem. Empirically, the work in service ecosystems well-being focuses on how different factors affect the performance of the service ecosystem, specifically its ability to balance challenges and resources to maintain viability (Brodie et al , 2021; Finsterwalder and Tombs, 2021). An exception, Baccarani and Cassia (2017) show how resource integration affects service ecosystem well-being and the well-being of specific focal actors (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the service ecosystems literature, most studies investigate value co-creation and not value co-destruction (Dodds et al , 2022; Finsterwalder and Kuppelwieser, 2020; Finsterwalder and Tombs, 2021; Vargo and Akaka, 2012). The only exception is the study by Echeverri (2021), which examines value co-destruction in interconnected transport and health-care service ecosystems; however, this study does not examine well-being as an outcome of these processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recently, Dodds et al (2022) found that service organizations have the potential to make a positive impact on the well-being of individuals, businesses and society. Furthermore, within a service ecosystem, the various actors can converse with one another and collaborate on improving well-being (Finsterwalder and Tombs, 2021). In fact, the concept of ecosystem well-being has been identified within the various components of retail service.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…More recently, some streams of research in the service discipline have focused on the “bigger picture” and investigated how service systems respond to disruptions and can restore balance to achieve service ecosystem well-being, regeneration and sustainability (Field et al , 2021; Finsterwalder and Tombs, 2021; Frow et al , 2019; Leo et al , 2019). Some of this research has also focused on the disruptions caused by COVID-19 (Brodie et al , 2021; Finsterwalder and Kuppelwieser, 2020).…”
Section: Service Marketing and The Winds Of Changementioning
confidence: 99%